Physiological quality of Physalis peruviana seeds under water stress conditions (Research, Society and Development, 2022)
Physalis peruviana is a herbaceous, shrubby and perennial plant belonging to the Solanaceae family. Its fruits have high nutritional value and medicinal properties. Due to its growing importance and propagation being sexual high-quality seeds are sought. The early stage of seedling development is delicate and of great importance; in the field they are subjected to several factors that may interfere with their development such as water stress. The aim was to evaluate the effect of water stress on physiological quality of P. peruviana seeds. Seeds were submitted to accelerated aging test conducted at 41 °C and 100% RH for 0; 48; 72 and 96h in order to obtain different batches. Water stress was induced with PEG-6000 with four osmotic potentials: 0.0 (control); -0.2; -0.4 and -0.6 MPa. Seed germination and vigor were evaluated (first count, shoot and root length). Accelerated aging reduced germination percentage as exposure time increased. It is concluded that seed batches of P. peruviana with the highest physiological quality showed better performance under water stress induced by PEG 6000 up to the potential -0.2 MPa. Water restriction caused a smaller growth of seedlings in the aerial part however, when seeds were submitted to the -0.2 MPa potential there was an increase in root length.